Stochastic analysis results for coordination of single-phase rooftop PVs in unbalanced residential feeders - Safitri, N.; Shahnia, Farhad; Masoum, Mohammad Sherkat (2016)
© 2015 IEEE.Installation of single-phase rooftop photovoltaic (PV) systems in low voltage (LV) residential feeders without controlling their ratings and locations may deteriorate the overall grid performance including reversed power flows, high losses and unacceptable voltage profiles. Therefore, in recent years the utilities have adopted limitations on the maximum allowable number of PVs in LV networks. To overcome these issues, this paper investigates the performance of a communication-based and intelligent voltage profile regulating technique under a Monte Carlo-based stochastic framework. This technique is applicable for LV residential feeders with single-phase rooftop PVs and relies on the availability of smart meters along the LV feeder to transmit phase voltage measurements to the controllers of the PV inverters. The objective of the voltage regulating technique is to minimize voltage unbalance along the feeder. The effectiveness and limitations of the voltage regulating method are investigated in this paper by the help of MATLAB-based simulation studies.